Investigating Students’ Attitude and Motivation in Learning English as a Second Language among Four Higher Institutions in Malaysia - Zulida binti Abdul Kadir; Rosmahalil Azrol bin Abdullah; Sarala @Thulasi Palpanadan; Siti Sara binti Zainal Abidin; Siti Salmiah binti Muhammad; Abdullah Adnan bin Mohamed (PAROLE: Journal of Linguistics and Education, 2020)
The aim of this study is to examine the students’ motivation and attitude towards learning English as a second language from four Malaysian higher institutions. A random sampling of 471 respondents participated in this study. Using 28 items instrument, adapted from Gardner’s Attitude/Motivation Test Battery (AMTB), an online questionnaire was distributed in getting the data. Students’ motivational level is found to be high with (M=6.37, SD=0.77, M=6.10, SD=0.82). Additionally, the respondents are having positive attitudes in learning English (M=4.07, SD=0.48).  With the findings, it is a hope that this can be a guidance for instructors to design a suitable lesson and approach to be used in the class.